Computational Modeling Intervertebral Disc Pathophysiology: A Review - Volz, Mallory; Elmasry, Shady; Jackson, Alicia R.; Travascio, Francesco (Frontiers in Physiology, 2022)
Lower back pain is a medical condition of epidemic proportion, and the degeneration of the intervertebral disc has been identified as a major contributor. The etiology of IVD degeneration is multifactorial, depending on age, cell-mediated molecular degradation processes and genetics, which is accelerated by traumatic or gradual mechanical factors. The complexity of such intertwined biochemical and mechanical processes leading to degeneration makes it difficult to quantitatively identify cause-effect relationships through experiments. Computational modeling of the intervertebral disc is a powerful investigative tool since it offers the opportunity to vary, observe and isolate the effects of a wide range of phenomena involved in the degenerative process of discs. This review aims at discussing the main findings of computational models of IVD pathophysiology with a special focus on the different factors contributing to physical changes typical of degenerative phenomena. Models presented are subdivided into those addressing progressive biochemical alterations stemming from an imbalance between anabolic and catabolic processes, and those considering mechanical factors as the primary source that induces morphological change within the disc. Limitations of the current models, as well as opportunities for future computational modeling work are also discussed.